The central hemodynamics assessment methods in thyrotoxicosis patients under inhaled anesthesia - Tarasenko, Sergii; Dubrov, Sergii; Kunatovskyi, Mikhailo; Efimova, Olena (ScienceRise: Medical Science, 2017)
Aim: To assess the central hemodynamics using calculation forms and invasive-noninvasive systems on the background of using inhaled minimal-streaming anesthesia at thyroidectomies in patients with thyrotoxicosis. Materials and methods. The study included 44 patients with the syndrome of thyrotoxicosis (diffuse thyrotoxic goiter – 31 patients (70,45 %), multi-node goiter – 10 (22,74 %) and toxic adenoma – 3 patients (6,81 %)), operated under the general anesthesia as inhaled anesthesia by sevoflurane by the method of minimal stream (FGF=400 ml/min., Sev 3,0 vol%). Women – 40 patients (91,9 %), men – 4 (9,1 %) patients. Mean age 47,61±2,39 years, BMI 25,89±0,53 c.u, body surface area 1,82±0,02 m2. The assessment of systolic arterial pressure (АPs), diastolic (APd), mean AR (MAP), sphygmic pressure (SP), HR, mean pressure in the aorta, (MPA). There was studied the index of the proper minute volume of blood circulation (PMCB) based on values of the proper main metabolism (PMM). The parameters of the central hemodynamics were studied intraoperationally (after patient’s intubation) after esophageal dopplerography on the apparatus Cardio Q ("Deltex Medical", Great Britain) and esCCO™ method (monitor Vismo, Nihon Kohden). esCCO™ method (calculative continuous heart ejection) and calculative formulas by: Starr, Lillier-Shtrander, Tsander, RU No. 2481785. Results and discussion. Calculative indices by M.M. Savitsky formula don’t reliably differ comparing with the objective instrumental method of hemodynamics control by DopplerEchoCG and can be used as initial indices for the comparison with instrumental and calculative ones. At the analysis of APs, APd, MAP, SP in control points, it was observed, that at patient’s admission to a surgical room MAP and MPA on 2 control reliably (р<0,001) increased by 7,3 % and 6,7 % respectively comparing with 1 control, connected with the natural anxiety of a patients before the surgical intervention. After the input anesthesia the reliably (р<0,001) lowest indices of MAP, MPA, SP, APs, APs on 3 control by Wilcoxon criterion were observed. They were stabilized at following stages of anesthesia. MVB and HI on all control points, according to the data of calculative formulas by Starr, Lillier-Shtrander and Tsander, have reliably (p<0,05) lower values by Wilcoxon criterion than according to instrumental data by DopplerEchoCG. The calculative indices MVB and HI, according to the RU No.2481785 have reliably (p<0,05) higher values by Wilcoxon criterion on all control points than by DopplerEchoCG instrumental data. MVB, GPVR, HI, obtained using the method of esCCO Vismo monitoring had the least degree of deviations from DopplerEchoCG data. Spearmen correlation between these indices was 0,83 (strong direct connection, p<0,05). Spearmen correlation is absent between indices of the calculative formulas of Starr, Lillier-Shtrander and Tsander and data of DopplerEchoCG (rs=–0,07 and rs=–0,14 respectively). The indices by the data of the patent RU No.2481785 have rather high mistake by the data of DopplerEchoCG comparing with esCCO method, but demonstrate the moderate correlation with them rs=0,38 (p<0,05). There is the strong direct correlation between indices of the invasive CardioQ EDM and non-invasive esCCO method (rs=0,75;p<0,05). Among calculative indices, the most correlation with data of esCCO method is demonstrated by indices by the patent С RU No. 2481785 (rs=0,38, p<0,05), indices by Starr, Lillier-Shtrander and Tsander formulas have no correlation with esCCO method. Conclusions. Calculative indices by M. M. Savitsky formula don’t reliably differ comparing with DopplerEchoCG data and can be used as initial indices for the comparison with instrumental and calculative ones. Calculative indices by the data of Starr, Lillier-Shrander and Tsander formulas underestimate MVB, HI and have no correlations comparing with instrumental assessment methods. Indices by the patent RU No.2481785 give overestimated values of MVB and HI, but have the moderate correlation (rs=0,38; (p<0,05) with both DopplerEchoCG and esCCO data. After the input anesthesia there is observed the reliable (p<0,05) decrease of MVB and HI by doth data of invasive monitoring – esophageal dopplerography by Cardio Q system, and non-invasive esCCO™ monitoring method (calculative continuous hearth ejection), stabilized at 5-6 stages of the operation. There is the moderate correlation between indices of data of invasive (Cardio Q) and non-invasive (esCCO™) monitoring at the level rs=0,75 (p<0,05). esCCO method allows to study fluctuations of the central hemodynamics at equal stages of anesthesia maximally effectively, it is a simple non-invasive method of control of the central hemodynamics with the high degree of correlation with DopplerEchoCg indices